The Implementation Of Land And Money Waqf Implementation On Society In Indonesia - sugianto, sugianto (Institut Agama Islam Sumatera Barat, 2025)
One of the fastest growing instruments of Islamic philanthropy in contemporary economic practice is waqf. This development is characterized by the presence of cash waqf and land waqf. This research aims to analyze the implementation of land waqf and cash waqf in the perspective of shari'ah law and positive law in Indonesia, as well as their effects on social welfare. This research is a descriptive qualitative study with a literature approach, using content analysis to describe the phenomenon of waqf. Data is collected through literature study of books, journals, and laws, then analyzed systematically. The results of this study are; first, the implementation of waqf management for the community in Indonesia still faces a number of challenges, such as the low literacy of waqf among the community, the weak governance system, and the lack of synergy between the waqf management institution and the government. Second, land waqf is permanent and benefits the people, while cash waqf is more flexible and productive. Both are social worship with the aim of benefit according to sharia principles. Third, land and cash waqf in Indonesia are regulated through Law No. 41 of 2004 and related regulations, with management based on sharia principles and transparency. Land waqf is permanent and physically used, while cash waqf is flexible and managed through sharia-based investments